KARAKTERISTIK BATANG PENTANAHAN SISTEM ARANG-GARAM (SIGARANG) SEBAGAI UPAYA PERBAIKAN SISTEM PENTANAHAN - Zainal Abidin (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2017)
The research was conducted in Lamongan regency in the south of Sarirejo Village and Mantup Subdistrict of Lamongan Regency, which is a sample of most of the soil conditions in the area which is dry with an average water depth of 100 m, so in the case of electric ground becomes less ideal. According to PUIL 2000 that the grounding on the infiltration of the recommended house at least 5? and a maximum of 10?. The use of a charcoal system grounding model (SIGARANG) becomes an earthing alternative that can be used for earthing household installation systems. Based on the result of the research, it is concluded that ground water, salt and charcoal with the size of 5: 2: 1 yields an average resistivity value of 1.52 ? on soil of wet soil conditions in Table 4.1, and an average of 2.43? on wetland of wet conditions in Table 4.3. compared with the method without the mean of the average value on 3? and 3 tanah lime soils. Grounding using water, salt and char (SIGARANG) can produce 75% earthing efficiency in limestone soils. The earth earthing efficiency of the soil is 65% on average compared to groundless earth.